PENGARUH BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MAUFAKTUR YANG TERDAFTAR DI BEI (BURSA EFEK INDONESIA) - KUSUMANINGTYAS, WULANDINI (Jurnal Akuntansi UMMI, 2022)
This study aims to analyze Effect of Deferred Tax Expense and Tax Planning Of Profit Management of Manufacturing Listed on the BEI (Indonesia Stock Exchange). This research uses quantitative methods and use secondary data as a source of data. The sampling technique used with purposive sampling method. Where a population of 182 companies, while the sample as many as 41 companies manufacturing listed on the Indonesia Stock Exchange. The results show that deferred tax expensed does not significant effect on earnings management and tax planning has a significanteffect on earnings management.